2012
DOI: 10.1093/jac/dks087
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-encoded PER-7  -lactamase responsible for ceftazidime resistance in Acinetobacter baumannii isolated in the United Arab Emirates

Abstract: Ceftazidime resistance was mediated by a PER-7 β-lactamase encoded in an ISCR1 element located on a plasmid. This represents the first detection of a PER-7 β-lactamase encoded by a plasmid in A. baumannii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…Hence, further phenotypic surveillance combined with molecular analyses were carried out to identify the emergence of such MDR bacteria. Recently, Opazo et al (64) identified three carbapenemase-producing Acinetobacter isolates from Al Ain. One was obtained from a catheter tip of an adult patient, and the other two were isolated from sputum of a pediatric patient a few weeks apart.…”
Section: Carbapenem Resistance In P Aeruginosa and Acinetobactermentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, further phenotypic surveillance combined with molecular analyses were carried out to identify the emergence of such MDR bacteria. Recently, Opazo et al (64) identified three carbapenemase-producing Acinetobacter isolates from Al Ain. One was obtained from a catheter tip of an adult patient, and the other two were isolated from sputum of a pediatric patient a few weeks apart.…”
Section: Carbapenem Resistance In P Aeruginosa and Acinetobactermentioning
confidence: 99%
“…These were identified by PFGE as the same clone, and all isolates carried the chromosomal bla OXA-64 gene and the bla OXA-23 gene on plasmids. Typically, the insertion sequence ISAba1 was found located upstream of the bla OXA-23 gene (64).…”
Section: Carbapenem Resistance In P Aeruginosa and Acinetobactermentioning
confidence: 99%
“…The first subgroup (PER-3, PER-4, PER-5, PER-7, and PER-8) is formed by replacing one or four amino acids in PER-1, and the other subgroup (PER-2 and PER-6) has only 86% similarity to PER-1 (6). Although PER-1 is prevalent in Europe and Asia (10)(11)(12), PER-2 has only been reported in South America, and PER-3, PER-6, and PER-7 have only been found sporadically (13)(14)(15)(16). Diverse mechanisms are responsible for the dissemination and acquisition of bla PER .…”
mentioning
confidence: 99%
“…Previous studies reported that bla PER-1 was a part of the composite transposon Tn1213 located in a chromosome or carried by plasmids (17). Recently, the ISCR1 element inside a sul1-type integron structure was found to play a role in the dissemination of bla PER-1 , bla PER-3 , and bla PER-7 (14,16,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation